Comparison of IAGOS in-situ water vapour measurements and ECMWF ERA-Interim Reanalysis data - Reutter, P.; Neis, Patrick; Rohs, Susanne; Sauvage, B. (EGU, 2019)
Abstract. Cirrus clouds and their potential formation regions, so-called ice-supersaturated regions (ISSRs) occur frequently in the tropopause region. It is assumed that ISSRs and cirrus clouds can change the tropopause structure by diabatic processes, driven by latent heating due to phase transition and interaction with radiation. For many research questions a three-dimensional picture including a sufficient temporal resolution of the water vapour fields in the tropopause region is required. This requirement is fulfilled nowadays by reanalysis products such as the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-Interim reanalysis. However, for a meaningful investigation of water vapour in the tropopause region a comparison of the reanalysis data with measurement is advisable, since it is difficult to measure water vapour and to assimilate meaningful measurements into reanalysis products. Here, we present an intercomparison of high-resolution in-situ measurements aboard passenger aircraft within the European Research Infrastructure IAGOS (In-service Aircraft for a Global Observing System; http://www.iagos.org) with ERA-Interim. Temperature and humidity data over the North Atlantic from 2000 to 2010 are compared relative to the dynamical tropopause. The comparison of the temperature shows a good agreement between measurement and ERA-Interim. While ERA-Interim can reproduce the main features of the water vapour measurements of IAGOS, the variability of the data is underestimated by the reanalysis data. The combination of temperature and water vapour leads to the relative humidity with respect to ice (RHi). Here ERA-Interim deviates from the measurements concerning values of larger than RHi=100 %, both in number and strength of supersaturation. The comparison of ISSR pathlengths shows distinct differences, which can be traced back to the spatial resolution of both data sets. IAGOS shows significantly more smaller ISSRs compared to ERA-Interim. A good agreement begins only at pathlengths in the order ...